THE EFFECT OF PICTURE WORD INDUCTIVE MODEL (PWIM) ON STUDENTS’ WRITING SKILL AT SEVENTH GRADE STUDENTS OF SMPN 14 BENGKULU CITY - Heru Kurniawan; Risnawati; Andriadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Writing skills are one of the basic competencies that are important for students, but there are often difficulties that become challenges for students. This research aims to determine whether there are significant differences in students' writing skills using the Picture Word Inductive Model (PWIM) in class VII students at SMPN 14 Bengkulu City. PWIM, as stated by Calhoun (1999), is designed to teach reading, writing and language system skills in an integrated manner by utilizing pictures and words as teaching aids. This research method uses a quasi-experimental approach to assess the significance of using PWIM in improving students' writing skills. This research involved two groups, namely an experimental class taught using PWIM and a control class taught using conventional methods, and was carried out in the 2023/2024 academic year. The results of the analysis show that there is a significant average difference between the two groups, where students taught with PWIM show better improvement in writing skills than students taught with conventional methods. Based on these results, it can be concluded that PWIM is effective in improving the writing skills of class VII students at SMPN 14 Bengkulu City.